2020
DOI: 10.1007/s40753-020-00118-5
|View full text |Cite
|
Sign up to set email alerts
|

How Does a Mathematician Fit in? A Mixed-Methods Analysis of University Students’ Sense of Belonging in Mathematics

Abstract: University mathematics has been described as a setting that has challenges in inviting everyone to be part of the mathematics community. Thus, university mathematics offers an important context for research on belonging. For this study, we utilised a mixed-methods approach to investigate the various ways mathematics students belong or do not belong to the mathematics community. Based on both quantitative and qualitative analyses, three student profiles were identified: Members of the Scientific Community, Memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Social relationships that facilitated a sense of belonging tended to be emotionally dense (Antonsich 2010): these included relationships with family and usually a small number of close friends, but also included weaker social ties such as mentors, academic staff and other friends. Where our findings diverge from other studies on belonging in higher education (Hurtado and Carter 1997;Lahdenperä and Nieminen 2020) is in suggesting that students actively chose to belong or not in various social contexts, both inside and outside the university setting. This indicates a level of agency and self-sufficiency that might be distinct from other non-autistic students.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Social relationships that facilitated a sense of belonging tended to be emotionally dense (Antonsich 2010): these included relationships with family and usually a small number of close friends, but also included weaker social ties such as mentors, academic staff and other friends. Where our findings diverge from other studies on belonging in higher education (Hurtado and Carter 1997;Lahdenperä and Nieminen 2020) is in suggesting that students actively chose to belong or not in various social contexts, both inside and outside the university setting. This indicates a level of agency and self-sufficiency that might be distinct from other non-autistic students.…”
Section: Discussioncontrasting
confidence: 99%
“…Earlier studies have reported that students in higher education might feel stigmatisation amongst their peers (Kendall 2016). However, May (2011) argues that a 'feeling of not belonging' need not always be experienced negatively, and that the tension between wanting to belong and wanting to be different from others can also be productive (Lahdenperä and Nieminen 2020). This resonates strongly with Ahn and Davis's (2020) final category of personal space, which they take to mean independence and the courage to be oneself.…”
Section: The Dimensions Of Belonging In Higher Educationmentioning
confidence: 85%
See 1 more Smart Citation
“…Our analytical focus is on stabilised and strong exclusionary discourses of ableism that overshadow disabled students' situated belonging (Nieminen, 2021;Dolmage, 2017;Slee, 2019). An important aspect of this endeavour is understanding the productive aspects of non-belonging: Not all university students want to belong to the university setting, nor take part in the social learning environments (Lahdenperä & Nieminen, 2020). Healy (2020) separated between non-belonging (loss of belonging) and un-belonging (removal of belonging), reminding us about the productive affordances of non-belonging to one's well-being.…”
Section: Sense Of Belonging and Learning Environments: Toward Socio-political Approachesmentioning
confidence: 99%
“…Yet while the barriers to learning for disabled students have been studied extensively in HE, until recently, the aspect of belonging has been understudied (Pesonen et al, 2020). Recent studies have advocated for learning environment design to support the belonging of all students; this idea has supplemented large campus-wide development programmes for belonging by promoting the importance of pedagogical design (Lahdenperä & Nieminen, 2020). For instance, Motta and Bennett (2018) discussed pedagogies of care, seeing teaching as an affective and embodied practice that holds the power to promote students' belonging.…”
Section: Introductionmentioning
confidence: 99%